(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article develops the features of architectural planning of the residential and functional environment of rural settlements in Uzbekistan. All types of construction work, in turn, increase the demand for high-quality construction products. Improving the living conditions of the population in rural areas presupposes the implementation of serious socio-economic transformations in our republic.